Selective laser trabeculoplasty versus argon laser trabeculoplasty in patients with open-angle glaucoma: a systematic review and meta-analysis. - Wei Wang; Miao He; Minwen Zhou; Xiulan Zhang (PLoS ONE)
Objective To examine possible differences in clinical outcomes between selective laser trabeculoplasty (SLT) and argon laser trabeculoplasty (ALT) in open-angle glaucoma at different times post-treatment. Methods Randomized controlled trials (RCTs) comparing SLT versus ALT were searched through August 2013. The main outcome measure was IOP, and secondary outcomes included the number of glaucoma medications, the success rate, and adverse events. Results Six RCTs, involving 482 eyes treated with laser trabeculoplasty, were included in the meta-analysis. For all patients (including first and previous laser trabeculoplasy), no significant difference in IOP lowering was observed between SLT and ALT at one hour (P = 0.40), one week (P = 0.72), one month (P = 0.37), six months (P = 0.08), one year (P = 0.34), two years (P = 0.58), three years (P = 0.34), four years (P = 0.47), and five years (P = 0.50). A statistically significant difference in favor of SLT was found when comparing the IOP reduction at three months after intervention (weighted mean difference (WMD): 1.19 mmHg [0.41; 1.97]; I(2)=0%; P = 0.003). For patients who were naive to laser, there was no significant difference of reduction in IOP comparing SLT with ALT at any time point. In patients' previous LT, no statistically significant difference in IOP reduction was found at six months (WMD: 1.92 mmHg [-0.91; 4.74]; I(2) = 77.3%; P = 0.18). There was no significant difference in the reduction in the number of glaucoma medications, the success rate, or adverse event rates between the two treatments. Conclusions SLT has equivalent efﬁcacy to ALT with a similar constellation of side effects. In the case of retreatment, SLT appears to be similar to ALT in IOP lowering at six months.